Montréal fin de siècle: histoire de la métropole du Canada au dix-neuvième siècle; ouvrage illustré (Gazette Printing, 1899)
Keywords: Métropole

Le bureau des pauvres de Montréal - Bellemarre, Raphaël (Bulletin des recherches historiques, 1899)
Keywords: Bureau des pauvres

Hochelagans and Mohawks; A Link in Iroquois History - Lighthall, W. D. (Mémoires et comptes rendus de la Société royale du Canada, 1899)
Keywords: Autochtones; Hochelaga; Iroquoiens

Histoire de Jos. Montferrand, l'athlète canadien - Sulte, Benjamin (Beauchemin, 1899)
Keywords: Montferrand; Joseph

Mère de la Nativité et les origines des soeurs de Miséricorde 1848-1898 (Imprimerie des sourds-muets, 1898)
Keywords: Communautés religieuses; Nativité; Mère de la; Soeurs de Miséricorde

Souvenir des fêtes jubilaires du Collège Sainte-Marie de Montréal, 1848-1898 (s.é., 1898)
Keywords: Collège Sainte-Marie; Communautés religieuses; Jésuites

Le Sault-au-Récollet; ses rapports avec les premiers temps de la colonie: mission-paroisse - Beaubien, Ch. Ph. Trottier de (Beauchemin, 1898)
Keywords: Sault-au-Récollet

Mémorial des familles Casgrain, Baby et Perreault du Canada - Casgrain, Philippe-Baby (Intime, 1898)
issued: 1898/1899
Keywords: Baby (famille); Casgrain (famille); Perrault (famille)

The Origin and Services of the 3rd Montreal Field Battery of Artillery - Chambers, Ernest J. (s.é., 1898)
Keywords: Milice; Montreal Field Battery of Artillery

Marie de la Nativité et les origines des soeurs de Miséricorde, 1848-1898 - Fournet, P.-A. (Imprimerie de l'Institution des sourds-muets, 1898)
Keywords: Cadron; Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde

Mother Nativity and the Origin of the Community of the Sisters of Miséricorde, 1848-1898 - Fournet, Pierre-Auguste (Institution for Deaf Mutes, 1898)
Keywords: Cadron; Marie-Rosalie; Communautés religieuses; Soeurs de Miséricorde

A New Hochelagan Burying-Ground Discovered at Westmount, 1898 - Lighthall, W. D. (s.é., 1898)
Keywords: Autochtones; Cartes et plans; Cimetières; Hochelaga; Iroquoiens

Historical and Descriptive Notice on the Church of Notre-Dame of Montreal (s.é., 1897)
Keywords: Notre-Dame (église); Églises

History of Montreal, Including the Streets of Montreal, their Origin and History - Borthwick, J. Douglas (D. Gallagher, 1897)
Keywords: Rues

Guide de Montréal et de ses environs - Leblond de Brumath, Adrien (Granger frères, libraires-éditeurs, 1897)

Souvenir de Maisonneuve. Esquisse historique de la ville de Montréal et séance d'inauguration du monument de M. de Maisonneuve, le 1er juillet 1895 (Desbarats, 1896)
Keywords: Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de)

Histoire de la charité à Montréal - Germano, J. (Revue canadienne, 1896)
Tome: 9
Keywords: Communautés religieuses

Life of the Venerable M.-M. Dufrost de Lajemmerais, Mde d'Youville - Ramsay, D.S. (Grey Nunnery, 1896)
Keywords: Communautés religieuses; Dufrost de Lajemmerais; Marie-Marguerite (Youville; Marguerite d'); Soeurs Grises

Une institution nationale: la Banque du peuple (Revue canadienne, 1895)
Keywords: Banque du Peuple; Banques

Annales des religieuses de Notre-Dame de Charité du Bon-Pasteur d'Angers - Gauthier, Henri (s.é., 1895)
Keywords: Soeurs du Bon-Pasteur

L'auberge de Joe Beef - Germano, Joseph (La revue nationale, 1895)
Keywords: Alcool; Auberges; McKiernan; Charles dit Joe Beef; Taverne Joe Beef

Les anciens postes du Lac Saint-Louis - Girouard, Désiré-H. (s.é., 1895)
Keywords: Saint-Louis (lac)

Fêtes jubilaires des religieuses de Notre-Dame de Charité du Bon Pasteur d'Angers à Montréal les 23, 24 et 25 juin 1894 (Religieuses de Notre-Dame de Charité du Bon Pasteur d'Angers, 1894)
Keywords: Communautés religieuses; Soeurs du Bon-Pasteur

Montreal Illustrated, 1894. Its Growth, Commerce, Manufacturing Interest, Financial Institution, Educational Advantages and Prospects (The Consolidated Illustrating Co., 1894)

Souvenir de Maisonneuve, esquisse historique de la ville de Montréal. Avec portraits et biographies de quelques-uns de nos Canadiens-français distingués.. (La compagnie de publication Maisonneuve, 1894)
Keywords: Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de)

La Miséricorde ou 50 années de dévouement et d'abnégation des religieuses de miséricorde à Montréal - Giroux, Henri (s.é., 1894)
Keywords: Communautés religieuses; Soeurs de Miséricorde

Histoire des travaux de la Commission du Havre dans le port de Montréal - Morin, L.-E. (Le Moniteur du commerce, 1894)
Keywords: Commission du Havre; Port

Histoire du commerce canadien-français de Montréal 1535-1895. Un souvenir - Saint-Pierre, Télesphore (Sabiston, 1894)

Illustrated Montreal, the Metropolis of Canada. Its Romantic History, its Beautiful Scenery, its Grand Institutions, its Present Greatness, its Future Splendour. 1892-1893 (John McConniff, 1893)

Notice sur les écoles relevant du bureau des commissaires catholiques romains de la cité de Montréal (Canada) (s.é., 1893)
Keywords: Commission des écoles catholiques de Montréal

Notices historiques sur l'Institution catholique des sourds-muets pour la province de Québec dirigée par les Clercs de Saint-Viateur, Mile-End, Montréal (Imprimerie de l'Institution des sourds-muets, 1893)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourds-muets; Sourds

Semi-Centennial Report of the Montreal Board of Trade. Sketches of the Growth of the City of Montreal from its Foundation, Statistics of Progress and Report of the Council for the Year Ending 31st December 1892 (Montreal Board of Trade, 1893)
Keywords: Montreal Board of Trade

L'église de St-François D'Assise de la Longue-Pointe - Bellay, A. (Revue canadienne, 1893)
Tome: 8
Keywords: Longue-Pointe; Saint-François-d'Assise (paroisse)

"ANOTE Kekon" - Cuoq, J.-A. (Mémoires et comptes rendus de la Société royale du Canada, 1893)
Keywords: Autochtones; Missions; Quéré de Tréguron; Maurice; Sulpiciens

Lake St. Louis, Old and New - Girouard, Désiré-H. (Poirier-Bessette, 1893)
Keywords: Saint-Louis (lac)

La cité de Saint-Cunégonde - Massicotte, E.-Z. (J. S. Houle, 1893)
Keywords: Sainte-Cunégonde

A Souvenir of the Opening of the New Building, One Thousand, Eight Hundred and Ninety-Three - Montreal Board Of Trade (Sabiston, 1893)
Keywords: Board of Trade

A Chronology of Montreal and of Canada from A.D. 1852 to A.D. 1893, Including Commercial Statistics, Historical Sketches of Commercial Corporations and Firms... - Terrill, Frederick William (Lovell, 1893)

Les soeurs de la Charité de la Providence. Histoire de l'hospice St-Jean-de-Dieu à la Longue-Pointe - Bellay, A. (Arbour & Laperle, 1892)
Keywords: Hôpital Saint-Jean-de-Dieu; Hôpitaux psychiatriques; Soeurs de la Providence

History and Biographical Gazeteer of Montreal to the Year 1892 - Borthwick, J. Douglas (Lovell, 1892)

Madame Gamelin et les origines de la Providence - Bourassa, Gustave (s.é., 1892)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

Historic Canadian Ground; the Lasalle Homestead of 1666 and Other Landmarks of French Canada on the Lower Lachine Road - Fraser, John (s.é., 1892)
Keywords: Cavelier de La Salle; René-Robert; Lachine

Les anciennes côtes du Lac Saint-Louis, avec un tableau complet des anciens et nouveaux propriétaires - Girouard, Désiré-H. (Poirier, Bessette & Co., 1892)
Keywords: Saint-Louis (lac)

Montreal After 250 Years - Lighthall, W. D. (F. E. Grafton and Sons, 1892)

Sights and Shrines of Montreal. A Topographical Romantic and Historical Description of the City and Environs, by W. D. Lighthall... - Lighthall, W. D. (F. E. Grafton, 1892)

Special Number of "The Dominion Illustrated" Devoted to Montreal the Commercial Metropolis of Canada (Sabiston, 1891)

Sieur de Maisonneuve et les origines de Montréal - Baker, William (Revue canadienne, 1891)
Tome: 4
Keywords: Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de)

Le Collège Sainte-Marie de Montréal - Bellay, A. (Revue canadienne, 1891)
Tome: 4
Keywords: Collège Sainte-Marie; Communautés religieuses; Jésuites

Les anciens forts de Lachine et Cavelier de La Salle - Girouard, Désiré (Eusèbe Sénécal et Fils, 1891)
Keywords: Cavelier de La Salle; René-Robert; Fortifications; Lachine

Hand-Book for the Use of Members and Visitors Giving the Rules of the Society, its History, and a Historical Sketch of Montreal with Places of Interest in its Vicinity - Royal Society Of Canada ((The Society), 1891)

Le siège du Long-Sault - Sulte, Benjamin (Pages d'histoire du Canada, 1891)
Keywords: Autochtones; Dollard Des Ormeaux; Adam

Illustrated Montreal, the Metropolis of Canada; its Romantic History, its Beautiful Scenery, its Grand Institutions, its Present Greatness, its Future Splendor (J. McConniff, 1890)

Souvenir Number of the Montreal Daily Star Reviewing the various Financial and Commercial Interests Represented in the City of Montreal (Henning J. Camp, 1890)
Keywords: Montreal Star

Histoire populaire de Montréal depuis ses origines jusqu'à nos jours - Leblond De Brumath, A. (Granger, 1890)

Jubilee History of Trinity Church, Montreal, 1840-1890 - Mott, Henry (s.é., 1890)
Keywords: Trinity Church; Églises

La famille de Callière - Sulte, Benjamin (Mémoires et comptes rendus de la Société royale du Canada, 1890)
Keywords: Callière; Louis-Hector de; Gouverneurs